2021
DOI: 10.1186/s12913-021-06526-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the correlation between effort-reward imbalance and sleep quality among community health workers

Abstract: Background A chronic state of imbalance between effort and reward can affect sleep quality. However, few studies have explored the relationship between variables in the work-related stress (the effort-reward imbalance model, ERI model) and sleep quality in community health workers in mainland China. We investigated the relationship between ERI and sleep quality in community health workers. Methods This cross-sectional study was conducted from Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…ERI is one of the more mature tools for evaluating occupational stress. Its content covers job responsibilities, workload, salary, development prospects, social recognition, sustainable job composition, and initiative and has good reliability and validity in previous studies on occupational stress of medical staff [ 37 , 38 ]. In China, occupational health research focused only on civil servants, administrative personnel, and teachers in the past [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…ERI is one of the more mature tools for evaluating occupational stress. Its content covers job responsibilities, workload, salary, development prospects, social recognition, sustainable job composition, and initiative and has good reliability and validity in previous studies on occupational stress of medical staff [ 37 , 38 ]. In China, occupational health research focused only on civil servants, administrative personnel, and teachers in the past [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A survey carried out in Shanghai demonstrates that 190 (61.7%) family doctors experienced excessive occupational stress [ 11 ]. Similarly, an investigation conducted in in southwestern China showed that 78.39% primary health workers had occupational stress [ 12 ]. Occupational stress also significant impact on staff mental and psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…If an ERR value greater than 1.0 indicated a high level of ERI. The prevalence of ERR value of > 1.0 among worker is widely prevailing, with a prevalence rate from 22.3% to 78.39% [ 12 , 16 , 17 ]. The ERI model is built on an imbalance between effort and reward caused a state of emotional distress from emotional and psycho-physiological stress reactions, which leads to a decrease in job satisfaction [ 18 , 19 ] and an increase in burnout [ 20 22 ] and turnover [ 23 ], and subsequently results an enormous variety of adverse health outcomes [ 24 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our data, showing that the ratio between effort and reward at work of above the value of 1.0 was present among 97 (82.9%) participants, is consistent with previous research. 43,44 A recent study among doctors and nurses by Deng et al 45 shows that 78.4% had a high ERI ratio and that the sleep quality worsened as the ERI ratio increased.…”
Section: Discussionmentioning
confidence: 99%